Mathematical Representation Ability Based on Self-Efficacy on Online Learning Through Flipped Classroom - Safrudin, M. Andi; Isnarto, Isnarto; Junaedi, Iwan (Universitas Negeri Semarang, 2021)
This research aims to describe the mathematical representation ability of students grade XI in online learning through a flipped classroom which was assisted by learning videos. It employed the mixed method specifically the concurrent embedded design. The subject of the research was determined based on the self-efficacy score from a self-efficacy questionnaire of the students grade XI at SMA N 1 Selomerto, Wonosobo. The tests, questionnaires and interviews were employed to collect the data. The effect of self-efficacy on mathematical representation ability was analyzed based on a simple linear regression test. The results showed that (1) students with high self-efficacy were able to master all indicators of mathematical representation well compared to students with moderate and low self-efficacy; (2) self-efficacy has a positive effect on the mathematical representation ability in online learning through flipped classroom.